2003
DOI: 10.1111/j.1346-8138.2003.tb00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma on the Right Hallux

Abstract: Basal cell carcinomas (BCCs) usually develop in sun-exposed areas. The finger, toe, and nail unit are very rare sites of BCC. We describe a patient with BCC on the right hallux. Clinically, it appeared as a brown-colored small plaque with an irregular border on the nail fold and dorsum of the right hallux. Histopathological findings were consistent with the superficial type of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The thumb was the most frequently affected site[568912131519242628] and the hallux was reported in five cases. [1118212227] The right middle finger was involved in three cases[41620] and both hands were affected with almost similar frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thumb was the most frequently affected site[568912131519242628] and the hallux was reported in five cases. [1118212227] The right middle finger was involved in three cases[41620] and both hands were affected with almost similar frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[111215172227] Classic features with a rolled out border were described only in a few of the reported articles. [111618] Thus, a skin biopsy should be carried out at the earliest hint of suspicion to diagnose these cancerous tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 To the best of our knowledge, basal cell carcinoma occurring in the nail unit has been reported in only 17 patients in the English literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We present a man with basal cell carcinoma of the nail unit and review the literature regarding the unique presentation of this tumor. We also discuss the common diagnostic difficulties when managing nail unit basal cell carcinomas.…”
mentioning
confidence: 99%
“…Skin cancer, predominantly basal cell carcinoma and squamous cell carcinoma, have accounted for about 40% of all cancers in the United States and their frequency has been increasing [1]. However, the nail unit is a very uncommon site for basal cell carcinoma to develop [2,3,4]. In 2006, Martinelli et al[ 2] reviewed the English literature and found only 17 patients with a basal cell carcinoma at this location.…”
Section: Introductionmentioning
confidence: 99%